2000
DOI: 10.1034/j.1600-0501.2000.011006521.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic characteristics of clinical and microbiological tests for monitoring periodontal and peri‐implant mucosal tissue conditions during supportive periodontal therapy (SPT)

Abstract: The aim of this study was to evaluate a clinical and a microbiological test for monitoring tissue condition during supportive periodontal therapy (SPT) and to compare their diagnostic characteristics at implant and tooth sites. Twelve female (age: 37-72 years) and 7 male patients (age: 26-83 years) were evaluated in this study on the basis of availability to follow a rigid SPT program. Patients had received a complete periodontal examination at 1 and 5 years after implant placement. This included standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 21 publications
3
97
0
6
Order By: Relevance
“…Additional clinical tests such as salivary analysis, peri-implant crevicular fluid analysis, and microbiological testing (Luterbacher et al 2000) have been suggested to be beneficial adjuncts to diagnosis and prediction of disease progression. Resonance frequency analysis has also been shown to detect minor changes in the level of boneimplant contact (Meredith et al 1996).…”
mentioning
confidence: 99%
“…Additional clinical tests such as salivary analysis, peri-implant crevicular fluid analysis, and microbiological testing (Luterbacher et al 2000) have been suggested to be beneficial adjuncts to diagnosis and prediction of disease progression. Resonance frequency analysis has also been shown to detect minor changes in the level of boneimplant contact (Meredith et al 1996).…”
mentioning
confidence: 99%
“…Bunun tam tersi olarak, sağlıklı implant dokularında sondalamada kanama kriterinin idame fazında tanısal önem taşıdığını mikrobiyolojik ve histolojik testlerle destekleyen çalışmalar da bulunmaktadır. 27,28 Yüksek Gİ skorlarına sahip implant grubumuzun yüksek SK skorlarına sahip olması beklenebilen bir sonuçtur. Bununla birlikte, Gİ ile SK arasında hem doğal dişler grubunda hem de implant grubunda pozitif yönde korelasyon bulunmuş-tur.…”
Section: Discussionunclassified
“…Numerosos estudios han encontrado una relación directa entre el SS y la pérdida de inserción alrededor del implante. Un estudio prospectivo cuyo objetivo fue monitorear las condiciones de la mucosa periimplantar durante la terapia periodontal de apoyo, reveló que el sangrado en un mismo sitio, en más de la mitad de las visitas de mantenimiento, durante un período de 2 años se relaciona con el progreso de la enfermedad (6) .…”
Section: Fig 5 Sangrado Al Sondaje Y/o Supuraciónunclassified
“…Numerous studies have found a direct link between bleeding on probing and suppuration and attachment loss around the implant. A prospective study that monitored the conditions of the peri-implant mucosa during supportive periodontal therapy found that bleeding on the same site, in over half of recall visits, in a period of two years, was related to the progression of the disease (6) .…”
Section: Fig 5 Bleeding On Probing And/or Suppurationmentioning
confidence: 99%